Validation of a Combined Transcriptome and T Cell Receptor Alpha/Beta (TRA/TRB) Repertoire Assay at the Single Cell Level for Paucicellular Samples - Litjens, Nicolle H. R.; Langerak, Anton W.; van der List, Amy C. J.; Klepper, Mariska; de Bie, Maaike; Azmani, Zakia; den Dekker, Alexander T.; Brouwer, Rutger W. W.; Betjes, Michiel G. H.; Van IJcken, Wilfred F. J. (Frontiers in Immunology, 2020)
Transcriptomics can be combined with TRA and TRB clonotype analysis at the single cell level. The aim of this study was to validate this approach on the ICELL8 Single-Cell system and to evaluate its usefulness to analyse clinical paucicellular samples. For this purpose, we carefully selected T cell lines with defined TRA/TRB clonotypes as well as clinical samples enriched for CD3+ T cells that possess a complex TCR repertoire. Low cell numbers of the different samples were dispensed in a chip on the ICELL8 Single-Cell System. Two sequencing libraries were generated from each single cell cDNA preparation, one for the TRA/TRB repertoire and one for the 5’ ends of transcripts, and subsequently sequenced. Transcriptome analysis revealed that the cell lines on average express 2268 unique genes/cell and T cells of clinical samples 770 unique genes/cell. The expected combined TRA/TRB clonotype was determined for on average 71% of the cells of the cell lines. In the clinical samples the TRA/TRB repertoire was more complex than those of the cell lines. Furthermore, the TRB clonotype distribution of the clinical samples was positively correlated to frequencies of TCRV families in CD3+ T cells obtained by a flow cytometry-based approach (Spearman’s Rho correlation coefficient 0.81, P=6.49 * 10-7). Combined analyses showed that transcriptome-based cell type-specific clusters in clinical samples corresponded to clinical features such as CMV status. In conclusion, we showed that the ICELL8 Single-Cell System enabled combined interrogation of both TRA/TRB repertoire and transcriptome of paucicellular clinical samples. This opens the way to study the response of single T cells within heterogeneous samples for both their transcriptome and TRA/TRB clonotypes in disease or upon treatment.